Pelatihan Design Sederhana Menggunakan Aplikasi Visual Studio 2010 dan SQL Server 2008 Pada Sekolah SMP IT Al Jabar - Yanyang Thanri; Lahmudin Sipahutar; Lili Tanti; Safrizal Safrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
At this time, along with the development of the times, technology has also developed very rapidly, especially in the field of computers. Where can we know that the development of this technology can help human work. In the world of education, computer science is very necessary so that teachers or students do not lag behind in the development of today's times. For this reason, training in computer science is needed. Many of us know computers only limited to Ms. Office alone because it is often used in everyday life, but actually in computer science there are many applications/programs that can help human work to be easier. For this reason, this training was made to introduce one of the application programs in computer science, namely the application of visual studio 2010 and SQL server 2008. Where this application can create programs according to our wishes to help make our work easier. The object that will be used as the location of service is the teachers at the Al JABAR Middle School. In this service, the team wants to do it in the form of training and talk shows about Simple Design Training Using Visual Studio 2010 and SQL Server 2008 Applications at IT AL JABAR Junior High School. The results obtained at the IT Al-Jabar Junior High School from this activity are that teachers can increase their knowledge in computer science, especially in making simple designs using Visual Studio 2010 and SQL Server 2008 applications which are useful for teaching materials to their students